2023
DOI: 10.1227/neu.0000000000002397
|View full text |Cite
|
Sign up to set email alerts
|

Are There Racial and Ethnic Health Disparities Among Outcomes After Anterior Cranial Fossa Surgery? A Propensity Score-Matched American College of Surgeons National Surgical Quality Improvement Program Study

Abstract: BACKGROUND: Race-based health care outcomes remain to be described in anterior cranial fossa (ACF) surgery. OBJECTIVE: To determine whether race predicts worse outcomes after ACF surgery. METHODS: A retrospective cohort study was performed using the American College of Surgeons National Surgical Quality Improvement Program data for 2005 to 2020. Current Procedural Terminology and International Classification of Diseases-9 codes were used to identify ACF tumor cases. Propensity score matching was performed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In the current study, the complication rate was 33%, with a mortality of 4.2%, which is in accordance with previous literature reports. Some recent studies have utilized the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database to analyze the complications; however, this database does not record surgical-specific complications for each procedure, like cranial nerve injury, CSF leaks, postoperative hematomas, or visual deficits [ 17 - 18 ]. Studies using the NSQIP database focus more on systemic complications, hospital length of stay, unplanned intubations, and ventilator dependence, therefore underestimating the overall complication rate [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the complication rate was 33%, with a mortality of 4.2%, which is in accordance with previous literature reports. Some recent studies have utilized the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database to analyze the complications; however, this database does not record surgical-specific complications for each procedure, like cranial nerve injury, CSF leaks, postoperative hematomas, or visual deficits [ 17 - 18 ]. Studies using the NSQIP database focus more on systemic complications, hospital length of stay, unplanned intubations, and ventilator dependence, therefore underestimating the overall complication rate [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Findlay et al observed longer length of stay (LOS) and fewer relative value units in minorities. 24 Tiwari et al demonstrated a higher DI incidence in Hispanic patients and those living in disadvantaged neighborhoods. 27 Haldar et al demonstrated that although Black patients had higher rates of postoperative emergency visits compared with White patients, they had comparable rates of readmission and reoperation.…”
Section: Postoperative Course and Outcomementioning
confidence: 98%
“…Six studies utilized the United States National Cancer Database (NCDB), [13][14][15][16][17][18] while 4 relied on Surveillance, Epidemiology, and End Results (SEER) programs. 13,[19][20][21] Two studies made use of the National Inpatient Sample (NIS) database, 22,23 and other studies used the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) 24 and the Statewide Planning and Research Cooperative System (SPARCS) database from the New York State Department of Health. 25 The Gantt chart demonstrates the temporal overlap between the included studies (Fig.…”
Section: Study Characteristicmentioning
confidence: 99%
See 2 more Smart Citations